Direct binding to antigen‐coated beads refines the specificity and cross‐reactivity of four monoclonal antibodies that recognize polymorphic epitopes of HLA class I molecules. Issue 4 (20th March 2013) - Hilton, H. G.; Parham, P.
Abstract Monoclonal antibodies with specificity for human leukocyte antigen (HLA) class I determinants of HLA were originally characterized using serological assays in which the targets were cells expressing three to six HLA class I variants. Because of this complexity, the specificities of the antibodies were defined indirectly by correlation. Here we use a direct binding assay, in which the targets are synthetic beads coated with 1 of 111 HLA class I variants, representing the full range of HLA‐A, ‐B and ‐C variation. We studied one monoclonal antibody with monomorphic specificity (W6/32) and four with polymorphic specificity (MA2.1, PA2.1, BB7.2 and BB7.1) and compared the results with those obtained previously. W6/32 reacted with all HLA class I variants. MA2.1 not only exhibits high specificity for HLA‐A*02, ‐B*57 and ‐B*58, but also exhibited cross‐reactivity with HLA‐A*11 and ‐B*15:16. At low concentration (1 µg/ml), PA2.1 and BB7.2 were both specific for HLA‐A*02 and ‐A*69, and at high concentration (50 µg/ml) exhibited significant cross‐reactions with HLA‐A*68, ‐A*23 and ‐A*24. BB7.1 exhibits specificity for HLA‐B*07 and ‐B*42, as previously described, but reacts equally well with HLA‐B*81, a rare allotype defined some 16 years after the description of BB7.1. The results obtained with cell‐based and bead‐based assays are consistent and, in combination with amino acid sequence comparison, increase understanding of the polymorphic epitopes recognized by the MA2.1, PA2.1, BB7.2 and BB7.1 antibodies. Comparison of two overlapping but distinctive bead sets from two sources gave similar results, but the overall levels of binding were significantly different. Several weaker reactions were observed with only one of the bead sets.